Identifying key factors in agent-based simulation model on processes in time-constrained environment - Loo Y.L.; Tang A.Y.C.; Ahmad A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Autonomous agents; Computational methods; Computer simulation; Efficiency; Processing; Robotics; Agent based simulation; Agent-based model; Agent-based simulation models; Conceptual model; time-constrained environment; Multi agent systems